Our 2014 approach to breakthrough invasive fungal infections. Issue 11 (25th June 2014) - Maschmeyer, Georg; Patterson, Thomas F.
Summary Evidence‐based clinical pathways to direct antifungal treatment options in patients with breakthrough fungal infections during current systemic antifungal therapy are not available. Nonetheless, for defined settings of such breakthrough infections approaches to management can be recommended based on clinical, epidemiological, pharmacological and in vitro susceptibility data.